Evaluating Factors for Prophylactic Feeding Tube Placement in Gastroesophageal Cancer Patients Undergoing Chemoradiotherapy - Verma, Vivek; Allen, Pamela K.; Lin, Steven H. (Frontiers in Oncology, 2017)
PURPOSE: Though better studied in head/neck cancers, there are currently no studies on timing of feeding tube (FT) placement in patients with gastroesophageal cancer. This study sought to discern characteristics of patients that used versus did not use a prophylactic FT (pFT), and also analyzed factors associated with placement of FTs during chemoradiotherapy (CRT). METHODS/MATERIALS: From 1998-2013, 1,329 patients underwent neoadjuvant CRT, of which 323 received a FT. Patients for whom FTs were placed prior to treatment due to tumor occlusion or substantial weight loss (n=130), and those with FTs placed following treatment (n=43) were excluded. One hundred patients had pFTs placed, and 50 underwent placement during CRT. The following was collected for each patient: demographic/patient information, oncologic/treatment characteristics, and CRT tolerance. RESULTS: No significant differences were found in any parameter between cohorts that used (n=66) versus did not use a pFT (n=34); on univariate and multivariate analyses, no pre-treatment characteristic associated with using a pFT. As compared with patients that used a pFT (n=66), those who required a FT during CRT (n=50) had lower body mass index (BMI) (p=0.045), underwent higher-dose RT (p=0.003), and received induction chemotherapy (p=0.031). On multivariate analysis, receipt of induction chemotherapy and greater weight loss and esophagitis during treatment were associated with placement of FTs during CRT (p<0.05). CONCLUSIONS: Of our cohort that received pFTs, there were no clinical factors that predicted for their use. Patients must be closely monitored for weight loss and esophagitis when receiving CRT in order to intervene prior to further worsening of toxicities.